The Impact of Clinical Practice Stress on Nursing Professional Competence among Undergraduate Nursing Students: A Cross-Sectional Study - Pei-Ling Wu (Florence Nightingale Journal of Nursing)
Aim: This study aims to explore the impact of undergraduate nursing students’ clinical practice stress on nursing professional competence.